Cerebrospinal Fluid Cytokine Expression Profile in Multiple Sclerosis and Chronic Inflammatory Demyelinating Polyneuropathy. - Bonin, Serena; Zanotta, Nunzia; Sartori, Arianna; Bratina, Alessio; Manganotti, Paolo; Trevisan, Giusto; Comar, Manola (Immunol Invest, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) analysis in patients with particular neurologic disorders is a powerful tool to evaluate specific central nervous system inflammatory markers for diagnostic needs, because CSF represents the specific immune micro-environment to the central nervous system. METHODS: CSF samples from 49 patients with multiple sclerosis (MS), chronic inflammatory demyelinating polyneuropathy (CIDP), and non-inflammatory neurologic disorders (NIND) as controls were submitted to protein expression profiles of 47 inflammatory biomarkers by multiplex Luminex bead assay to investigate possible differences in the inflammatory process for MS and CIDP. RESULTS: Our results showed differences in CSF cytokine levels in MS and CIDP; in particular, IL12 (p40) was significantly highly expressed in MS in comparison with CIDP and NIND, while SDF-1α and SCGF-β were significantly highly expressed in CIDP cohort when compared to MS and NIND. IL-9, IL-13, and IL-17 had higher expression levels in NIND if compared with the other groups. CONCLUSIONS: Our study showed that, despite some common pathogenic mechanisms, central and peripheral nervous system demyelinating diseases, such as MS and CIDP, differ in some specific inflammatory soluble proteins in CSF, underlining differences in the immune response involved in those autoimmune diseases.
Keywords: Adult; Aged; Biomarkers; Central Nervous System; Diagnosis, Differential; Female; Hematopoietic Cell Growth Factors; Humans; Interleukin-12; Lectins, C-Type; Male; Middle Aged; Multiple Sclerosis; Peripheral Nervous System; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Proteins